Who do you want to be when you grow old? : the path of purposeful aging - Leider, Richard; Shapiro, David, 1947- (Berrett-Koehler Publishers, 2021)
Grow old on purpose. This book invites readers to navigate a purposeful path from adulthood to elderhood with choice, curiosity, and courage. Everyone is getting old; not everyone is growing old. But the path of purposeful aging is accessible to all--and it's fundamental to health, happiness, and longevity. With a focus on growing whole through developing a sense of purpose in later life, Who Do You Want to Be When You Grow Old? celebrates the experience of aging with inspiring stories, real-world practices, and provocative questions. Framed by a long conversation between two old friends, the book reconceives aging as a liberating experience that enables us to become more authentically the person we always meant to be with each passing year. In their bestseller Repacking Your Bags, Richard J. Leider and David A. Shapiro defined the good life as "living in the place you belong, with people you love, doing the right work, on purpose." This book builds on that definition to offer a purposeful path for living well while aging well